Voluntary effort and rural development - Satyanarayana, G. (Jaipur : Rawat Publications, 2007)
Study with reference to Weaker Community's Action for Development and Liberation, voluntary organization located in Mahabubnagar District of Andhra Pardesh, India.
Includes bibliographical references (p. [286]-292) and index.
Keywords: Weaker Community's Action for Development and Liberation; Associations, institutions, etc. -- India -- Mahabubnagar (District); Rural development -- India -- Mahabubnagar (District); Rural poor -- India -- Mahabubnagar (District) -- Social conditions